PENGARUH PENGALAMAN KERJA, PENDIDIKAN DAN KEPRIBADIAN TERHADAP PENGEMBANGAN KARIR KARYAWAN PADA HOTEL NIKKI DENPASAR - Saraswati, Komang Andani; Dewi, A. A. Sagung Kartika (E-Jurnal Manajemen; Vol 6 No 11 (2017), 2017)
Employees are assets in the company that can bring the company's name to be good or bad in the eyes of the public. Because if the employee's performance is good then the company's performance will be good and vice versa. Companies need to implement career development programs and contribute to provide all the needs needed by employees to improve employee performance. The purpose of this study is to determine the effect of work experience, education, and personality on employee career development at Hotel Nikki in Denpasar. The sample used in this research is all employees of Hotel Nikki in Denpasar which amounts to 110 people with saturated sample technique (census). Data analysis technique used in this research is multiple linear regression analysis. The results of the analysis show that work experience, education, and personality have a positive effect on the career development of Hotel Nikki employees in Denpasar. Suggestions for all employees of Hotel Nikki is to further enhance the sense of responsibility, education, especially formal education, and logical, honest and thorough thinking in order to complete the tasks given well. For the management of the Hotel it is also advisable to pay attention to the work environment and the compensation of its employees to fit the current occupied position. Keywords: work experience, education, personality, career development.